2023
DOI: 10.1038/s41598-023-43277-6
|View full text |Cite
|
Sign up to set email alerts
|

An artificial intelligence model for the radiographic diagnosis of osteoarthritis of the temporomandibular joint

Wael M. Talaat,
Shishir Shetty,
Saad Al Bayatti
et al.

Abstract: The interpretation of the signs of Temporomandibular joint (TMJ) osteoarthritis on cone-beam computed tomography (CBCT) is highly subjective that hinders the diagnostic process. The objectives of this study were to develop and test the performance of an artificial intelligence (AI) model for the diagnosis of TMJ osteoarthritis from CBCT. A total of 2737 CBCT images from 943 patients were used for the training and validation of the AI model. The model was based on a single convolutional network while object det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In a preliminary study, Reda et al 13 demonstrated that AI can effectively identify TMDs early by accessing records of other clinical cases reported in the literature, thus providing a possible diagnosis based on symptoms. Likewise, Talaat et al 14 investigated the capacity of AI models to identify potential risks of osteoarthritis in the temporomandibular joint (TMJ) using computed tomography (CT)-considered the gold standard for investigation. Interestingly, these authors found that AI exhibited a greater degree of diagnostic accuracy compared with professional radiologists, in terms of both symptoms and the presence of morphostructural alterations (p = 0.0079 and p = 0.0214, respectively).…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…In a preliminary study, Reda et al 13 demonstrated that AI can effectively identify TMDs early by accessing records of other clinical cases reported in the literature, thus providing a possible diagnosis based on symptoms. Likewise, Talaat et al 14 investigated the capacity of AI models to identify potential risks of osteoarthritis in the temporomandibular joint (TMJ) using computed tomography (CT)-considered the gold standard for investigation. Interestingly, these authors found that AI exhibited a greater degree of diagnostic accuracy compared with professional radiologists, in terms of both symptoms and the presence of morphostructural alterations (p = 0.0079 and p = 0.0214, respectively).…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%